2020
DOI: 10.1186/s12967-020-02484-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel rabbit derived anti-HER2 antibody with pronounced therapeutic effectiveness on HER2-positive breast cancer cells in vitro and in humanized tumor mice (HTM)

Abstract: Background: Antibody based cancer therapies have achieved convincing success rates combining enhanced tumor specificity and reduced side effects in patients. Trastuzumab that targets the human epidermal growth factor related receptor 2 (HER2) is one of the greatest success stories in this field. For decades, trastuzumab based treatment regimens are significantly improving the prognosis of HER2-positive breast cancer patients both in the metastatic and the (neo-) adjuvant setting. Nevertheless, ≥ 50% of trastuz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The assay can be used to evaluate the effects of antibody glycosylation on their ADCC activity in early drug development (Chung et al, 2014). In addition, it has the performance characteristics (precision, accuracy, and linearity) required for a potency assay for lot release and stability study (Parekh et al, 2012;Prior et al, 2017;Wege et al, 2020).…”
Section: Adcc Reporter Bioassay Using Engineered Adcc Bioassay Effect...mentioning
confidence: 99%
“…The assay can be used to evaluate the effects of antibody glycosylation on their ADCC activity in early drug development (Chung et al, 2014). In addition, it has the performance characteristics (precision, accuracy, and linearity) required for a potency assay for lot release and stability study (Parekh et al, 2012;Prior et al, 2017;Wege et al, 2020).…”
Section: Adcc Reporter Bioassay Using Engineered Adcc Bioassay Effect...mentioning
confidence: 99%
“…Here, we quantitatively analyzed the expression and the secretion of different checkpoint molecules in humanized tumor mice (HTM) models specific for HER2 + , hormone receptor positive, and TNBC. HTM develop a human immune system and human tumor growth [16], and they have already enabled the identification of novel therapeutic antibodies [17], prognostic and potentially predictive markers [18], and probably side effects during immunomodulatory cytokine stimulation [19]. The expression of different checkpoint molecules has already been described in patient-derived (humanized) tumor mice (PDX) mice using multi-color-flow cytometry [20].…”
Section: Introductionmentioning
confidence: 99%
“…HER2 plays an important role in regulation of complex intracellular pathways in response to biochemical stimuli such as epidermal growth factor (EGF) and transforming growth factor (TGF- β ) for critical decision of cell fate within cancer cells [ 3 6 ]. Trastuzumab (TZB), the first humanized mono-clone antibody, selectively targets HER2 on cancer cells and provides successful survival benefits in HER2 + metastatic breast cancers [ 7 , 8 ]. It has been shown that TZB initiates the apoptosis signaling in cancer cells by suppressing the anti-apoptotic family, Bcl-2 members [ 9 ], which subsequently induces up-regulation of BAX, apoptosis inducer.…”
Section: Introductionmentioning
confidence: 99%